Expression of a human T-cell protein-tyrosine-phosphatase in baby hamster kidney cells. - Cool, D E (1990)
A human T-cell cDNA encoding a 48-kDa protein-tyrosine-phosphatase (PTPase; protein-tyrosine-phosphate phosphohydrolase, EC 3.1.3.48) was cloned into a mammalian expression vector and introduced into baby hamster kidney cells, and stable colonies were isolated. The expressed PTPase was found to be associated with the particulate fraction of the cells, where it was essentially inactive in an in vitro assay unless first subjected to limited trypsinization; trypsin treatment generated an active fragment of 33 kDa by the removal of a carboxyl-terminal segment of the full-length enzyme. Gel filtration indicated that the expressed enzyme was associated with a complex of greater than 600 kDa. Introduction of a premature stop codon into the T-cell cDNA at position 1012 resulted in the production of a fully active 37-kDa species that distributed between both the particulate and soluble fractions. The truncated form of the enzyme was readily solubilized by detergents and was eluted within its predicted molecular mass range. These results suggest that the carboxyl-terminal segment is important in determining the localization and regulation of the PTPase. The level of protein-tyrosine phosphorylation observed after 5 min of platelet-derived growth factor stimulation was reduced in cells overexpressing either form of the phosphatase, indicating that both are active in vivo. Overexpressing the truncated enzyme resulted in a growth rate that was approximately 50% of that observed in cells transfected with either the full-length PTPase cDNA or the vector alone.